MORAL EVIL DALAM PERSPEKTIF FILSAFAT DAN ISLAM: ANTARA KEHENDAK BEBAS, AMBIGUITAS MORAL, DAN SISTEM ETIKA ISLAM - Fauzul Kabir; Wahyu Trisno Aji; Amir Hamzah (Makkah: Journal Of Islamic Studies, 2026)
This paper discusses moral evil, starting from its definition, the standards of good and evil, to the Islamic perspective on moral evil. The study employs a philosophical–critical library research approach, with documentation data collected from journals, books, and websites. The results of this paper indicate that evil arises from human consciousness, caused by the inability to fully and properly utilize free will. Likewise, the standards of goodness remain ambiguous, as humans adopt differing and relative standards of good. In contrast, Islam classifies crimes systematically through ḥudūd, qiṣāṣ, diyāt, and ta‘zīr. Ultimately, evil always leads to consequences, and its prevention depends on strengthening faith (īmān), piety (taqwā), and human moral awareness.